2016
DOI: 10.1038/srep27967
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AtMed15 of Arabidopsis in yeast causes flocculation and increases ethanol production in yeast culture

Abstract: Mediator, a multiprotein complex involved in transcription of class II genes, was first discovered in yeast and then characterized in many metazoans revealing a striking structural conservation of the complex. However, sequences of Mediator subunits are not well conserved raising a question on the functional conservation of these individual subunits. In this study, expression of Med15 of Arabidopsis (AtMed15) in gal11∆ yeast could not complement the function of ScGal11 in galactose metabolism and resistance ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Recently, increased ethanol production was achieved in yeast by expression of AtMed15 of Arabidopsis which led to increased flocculation [9]. The resistance of yeast to high temperature and ethanol concentration are desirable characteristics for production of bioethanol [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increased ethanol production was achieved in yeast by expression of AtMed15 of Arabidopsis which led to increased flocculation [9]. The resistance of yeast to high temperature and ethanol concentration are desirable characteristics for production of bioethanol [10].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic improvement of yeast to obtain strains that can combat or adapt to extreme conditions of stress, is an important strategy to ensure the competitiveness of a fermentation process. Recently, increased ethanol production was achieved in yeast by expression of AtMed15 of Arabidopsis which led to increased flocculation [ 9 ]. The resistance of yeast to high temperature and ethanol concentration are desirable characteristics for production of bioethanol [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These and other studies found that MED15 was also required for flocculation and adhesion ( Barrales et al, 2008 ; Fidalgo et al, 2008 ). Finally, overexpression of Arabidopsis thaliana MED15 in wild type strains of S. cerevisiae led to increased flocculation, adhesion and a significant increase in ethanol production ( Dahiya et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, fermentable sugars can be obtained by enzymatic hydrolysis of inulin directly, which has the characteristics of simple process without high temperature liquefaction and low energy consumption. Compared with crop straw which is the representative of lignocellulosic biomass, ethanol production by inulin fermentation is easier to industrialize 911 . In addition, JA has the advantages of the high carbohydrate yields (5 and 14 ton/ha) and large-scale cultivation.…”
Section: Introductionmentioning
confidence: 99%